Simulation of multi-material hydrodynamic flows using adaptive mesh refinement - Povarnitsyn, M.E.; Zakharenkov, A.S.; Levashov, P.R.; Khishchenko, K.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2012)
A hydrodynamic multi-material model combined with a procedure of block-structured meshes construction implemented in the Chombo package is considered. The application of adaptive meshes allows one to efficiently redistribute computer resources as well as to save the machine memory when solving multi-dimensional problems.